2010
DOI: 10.1673/031.010.0901
|View full text |Cite
|
Sign up to set email alerts
|

Presence of the Aphid,Chaetosiphon fragaefolii, on Strawberry in Argentina

Abstract: Seasonal abundance of the strawberry aphid complex under different agronomic practices in the outskirts of La Plata, Argentina was studied on strawberry, Fragaria x ananassa Duchesne (Rosales: Rosaceae). Aphid densities were low in strawberry fields in which insecticides and fungicides were used. In addition to Aphis gossypii, Aphis fabae, Mysus persicae and Macrosiphum euphorbiae, the aphid, Chaetosiphon fragaefolii (Cockerell) (Homoptera: Aphididae), was recorded for the first time in this horticultural area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 14 publications
2
14
1
6
Order By: Relevance
“…These results are different from the results of Dixon (1987) and Minks and Harrewijn (1987), who reported that aphids generally undergo four nymphal instars, although part of the population will only undergo three (Kairo and Murphy, 1999). Bernardi et al (2012) observed four nymphal instars for C. fragaefolii on strawberry, however, Chagas Filho et al (2005) and Cédola and Greco (2010) reported the existence of a fifth instar. That is, although the most common is four instars for most aphids, it is found that variations can occur in quantities of the instars.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…These results are different from the results of Dixon (1987) and Minks and Harrewijn (1987), who reported that aphids generally undergo four nymphal instars, although part of the population will only undergo three (Kairo and Murphy, 1999). Bernardi et al (2012) observed four nymphal instars for C. fragaefolii on strawberry, however, Chagas Filho et al (2005) and Cédola and Greco (2010) reported the existence of a fifth instar. That is, although the most common is four instars for most aphids, it is found that variations can occur in quantities of the instars.…”
Section: Discussionmentioning
confidence: 62%
“…Cédola and Greco (2010) observed 11.8 days in the reproductive period of the C. fragaefolli. Bernardi et al (2012) found a cycle life of 17.17 days for C. fragaefolli in the cultivar Albion.…”
Section: Four Nymphal Instarsmentioning
confidence: 89%
See 1 more Smart Citation
“…O pulgão-verde Chaetosiphon fragaefolli (Cockerell, 1901) (Hemiptera: Aphididae) é o principal afídeo associado à cultura do morangueiro em diversos países, tais como Estados Unidos, Canadá, Argentina, Grã-Bretanha, África do Sul, Nova Zelândia e Austrália (RONDON;CANTCLIFFE, 2004;CÉDOLA;GRECO, 2010). No Brasil, a espécie é relatada como o principal inseto-praga da cultura (COSTA et al, 1993;BOTTON et al, 2010).…”
Section: Introductionunclassified
“…Aphids (Hemiptera: Aphididae) are considered key pests of strawberry plants (Botton et al 2010;Cédola and Greco, 2010). Among the aphid species related to this culture, Aphis forbesi Weed, 1889, a monophagous species known as root aphid (Botton et al, 2010) stands out.…”
mentioning
confidence: 99%